Increased sustainability in poultry production: new tools and resources for genetic management - Whyte, J; Blesbois, E; McGrew, M. J (Sustainable poultry production in Europe, 2016)
This chapter examines the emerging technologies that can be applied in the poultry industry in the coming decade for increased sustainability of genetic resources. Some of these technologies such as semen cryopreservation are currently being used for sustainable production by protecting and maintaining genetic variation in poultry populations and stem-cell biobanks are also under development. New genetic tools to modify the avian genome could potentially be used to introduce novel genetic variation and disease resistance into existing commercial flocks. Future challenges will lie in integration of these emerging technologies into existing production systems and addressing the regulatory policies in both regional and global markets.